Design, Development and Implementation of the Position Estimator Algorithm for Harmonic Motion on the XY Flexural Mechanism for High Precision Positioning - Mahesh Shewale; Ali Razban; Suhas Deshmukh; Sharad Mulik (Sensors, 2020)
This article presents a novel concept of the position estimator algorithm for voice coil actuators used in precision scanning applications. Here, a voice coil motor was used as an actuator and a sensor using the position estimator algorithm, which was derived from an electro-mechanical model of a voice coil motor. According to the proposed algorithm, the position of coil relative to the fixed magnet position depends on the current drawn, voltage across coil and motor constant of the voice coil motor. This eliminates the use of a sensor that is an integral part of all feedback control systems. Proposed position estimator was experimentally validated for the voice coil actuator in integration with electro-mechanical modeling of the flexural mechanism. The experimental setup consisted of the flexural mechanism, voice coil actuator, current and voltage monitoring circuitry and its interfacing with PC via a dSPACE DS1104 R&D microcontroller board. Theoretical and experimental results revealed successful implementation of the proposed novel algorithm in the feedback control system with positioning resolution of less than ±5 microns at the scanning speed of more than 5 mm/s. Further, proportional-integral-derivative (PID) control strategy was implemented along with developed algorithm to minimize the error. The position determined by the position estimator algorithm has an accuracy of 99.4% for single direction motion with the experimentally observed position at those instantaneous states.